Effects of inorganic iron and myoglobin on in vitro proximal tubular lipid peroxidation and cytotoxicity. - Zager, R A (1992)
Recent in vivo studies suggest that heme Fe causes proximal tubular lipid peroxidation and cytotoxicity, thereby contributing to the pathogenesis of myoglobinuric (Mgb) acute renal failure. Because hydroxyl radical (.OH) scavengers [dimethylthiourea (DMTU), benzoate, mannitol] can mitigate this injury, it is postulated that .OH is a mediator of Mgb-induced renal damage. The present study has tested these hypotheses using an isolated rat proximal tubular segment (PTS) system. An equal mixture of Fe2+/Fe3+ (4 mM total), when added to PTS, caused marked cytotoxicity [as defined by lactate dehydrogenase (LDH) release] and lipid peroxidation [assessed by malondialdehyde (MDA) increments]. Fe2+ or Fe3+ alone each induced massive MDA elevations, but only Fe2+ caused cytotoxicity. Although both DMTU and benzoate decreased LDH release during the Fe2+/Fe3+ challenge, mannitol and GSH did not, despite equivalent reductions in .OH (gauged by the salicylate trap method). GSH and catalase (but not DMTU, benzoate, or mannitol) decreased MDA concentrations, suggesting the Fe-driven lipid peroxidation was more H2O2 than .OH dependent. Deferoxamine totally blocked Fe-induced LDH release, even under conditions in which it caused an apparent increase in .OH generation. Mgb paradoxically protected against Fe-mediated PTS injury, an effect largely reproduced by albumin. In conclusion, these data suggest that: (a) Fe can cause PTS lipid peroxidation and cytotoxicity by a non-.OH-dependent mechanism; (b) Fe-mediated cytotoxicity and lipid peroxidation are not necessarily linked; and (c) Mgb paradoxically protects PTS against Fe-mediated injury, suggesting that: (i) Mgb Fe may require liberation from its porphyrin ring before exerting toxicity; and (ii) the protein residue may blunt the resulting injury.